2013
DOI: 10.1007/s00595-013-0799-7
|View full text |Cite
|
Sign up to set email alerts
|

Elastography for hepato-biliary-pancreatic surgery

Abstract: Palpation is a subjective and non-sharable diagnostic method. Recently, palpation has been supported and replaced by elastography, which provides a novel parameter of “stiffness” as a visual representation or quantified value. Today, elastography is performed using two major modalities: strain elastography and shear wave elastography. Strain elastography converts the extent of deformation during external compression into colors, displaying these colors as a strain map in a motion picture representing the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 78 publications
3
10
0
Order By: Relevance
“…The results suggested both the dried hydrogels had a capacity to expand bile ducts by swelling, because the controlled force corresponds to the force, which can expand bile ducts by twice. The vertical force applied in the swelling tests under a controlled expansion force (20 kPa on the specimen) is close to the previously reported maximal value of the elastic modulus of the gastrointestinal tissue, which varies widely (range: 0.6–20 kPa) . We set the controlled vertical force for the swelling tests based on the following facts and estimations.…”
Section: Discussionsupporting
confidence: 66%
“…The results suggested both the dried hydrogels had a capacity to expand bile ducts by swelling, because the controlled force corresponds to the force, which can expand bile ducts by twice. The vertical force applied in the swelling tests under a controlled expansion force (20 kPa on the specimen) is close to the previously reported maximal value of the elastic modulus of the gastrointestinal tissue, which varies widely (range: 0.6–20 kPa) . We set the controlled vertical force for the swelling tests based on the following facts and estimations.…”
Section: Discussionsupporting
confidence: 66%
“…Although the sensitivity was slightly lower, our findings are concordant with results from other authors who reported sensitivity rates of 42% up to 100% for localization and characterization of FPLs using endoscopic US or transabdominal US. 6,11,[12][13][14][15][16][17]27 We found intratumoral indurations of 3 m/s or 28.7 kPa to be reasonable cutoff values during intraoperative application, with a sensitivity rate of 74.4%, though the negative predictive value was only about 41%. These cutoffs can be interpreted as initial reference values for intraoperative pancreas tumor characterization and differential diagnosis using IoSWE, but the identification or confirmation of FPL malignancy was more accurate with IoCEUS.…”
Section: Discussionmentioning
confidence: 64%
“…Thereby, reproducible and quantifiable information about the FPLs' elasticity can be gained, which correlates with the benign or malignant nature of the lesion. 3,[11][12][13][14][15][16] Studies of recent literature proved this advantage of SWE, particularly for small FPLs. 14,17,18 Another important feature that helps distinguish malignant from benign FPLs is their microvascularization.…”
mentioning
confidence: 94%
See 2 more Smart Citations